Pengaruh Persepsi Tentang Penerapan Tarif Efektif Rata-Rata (TER) dan Tax Morale Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Talitha Tsani Azaria; Moh. Danang Bahtiar (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research is motivated by the suboptimal material compliance of individual taxpayers at the Mulyorejo Surabaya Tax Office (KPP Pratama), which is reflected in the gap between reporting and payment achievements. This study aims to analyze the influence of perceptions regarding the application of the Average Effective Rate (TER) and tax morale on individual taxpayer compliance. The study used a quantitative approach involving 200 individual taxpayers, both permanent and non-permanent employees, registered at the Mulyorejo Surabaya Tax Office. Data were collected through questionnaires and analyzed using multiple linear regression analysis preceded by validity tests, reliability tests, and classical assumption tests. The results showed that perceptions regarding the application of the Average Effective Rate (TER) did not significantly influence taxpayer compliance, while tax morale had a positive and significant effect on taxpayer compliance. Simultaneously, both variables significantly influenced individual taxpayer compliance. These findings indicate that increasing taxpayer compliance is more influenced by tax morale factors than perceptions regarding the application of TER. Therefore, it is necessary to strengthen socialization programs to build tax morale as well as evaluate the effectiveness of TER implementation in supporting tax compliance.